(untitled) (Mongolian Journal of International Affairs, 2013)
The major trends of the survey done by the Institute of Philosophy, Sociology and Law, Academy of Sciences, was on the state of political parties and their impact and responsibilities on the social process within the framework of a two-stage project implementation on the “Support in Achieving MDG-9 on human rights and democratic governance in Mongolia”. The process in the state of the political parties has naturally been implemented, and eventually there was no deadlock and interruption in the course of action. Within the survey results, it seems imperfection and insufficient promises in the level of unsatisfactory quality in significance of progression. DOI: http://dx.doi.org/10.5564/mjia.v0i18.69 Mongolian Journal of International Affairs No.18 2013: 47-51